A rare case of a giant ovarian dermoid cyst in a 65-year-old woman: a case report - N., Sunanda; Janvekar, Sadafara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian dermoid cysts, or mature cystic teratomas, are benign germ cell tumors containing tissues derived from ectoderm, mesoderm, and endoderm. While common in younger women, they are rare in postmenopausal individuals, with a small percentage exhibiting malignant potential. We present a case of a 65-year-old postmenopausal woman with a six-month history of an abdominal mass and intermittent pain. Physical examination revealed a large abdominopelvic mass, and imaging studies identified a 16.5×13.9×16.4 cm heterogenous solid mass arising from the left ovary, diagnosed as a dermoid cyst. Surgical intervention confirmed a 25×20×15 cm cyst containing characteristic contents, necessitating total abdominal hysterectomy with bilateral salpingo-oophorectomy. Similar cases in postmenopausal women underscore the diagnostic challenge and need for prompt evaluation and management. Imaging modalities such as ultrasound and CT scan play crucial roles in diagnosis, revealing typical features like fat components and dermoid mesh. Surgical excision remains the mainstay treatment, balancing risks of spillage and recurrence. This case highlights the importance of considering dermoid cysts in the differential diagnosis of abdominal masses in postmenopausal women. Early recognition and appropriate management are essential to prevent complications associated with these rare but potentially substantial ovarian tumors.